1998
DOI: 10.1046/j.1365-2958.1998.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair in Mycobacterium tuberculosis. What have we learnt from the genome sequence?

Abstract: SummaryThe genome sequence of Mycobacterium tuberculosis was analysed by searching for homologues of genes known to be involved in the reversal or repair of DNA damage in Escherichia coli and related organisms. Genes necessary to perform nucleotide excision repair (NER), base excision repair (BER), recombination, and SOS repair and mutagenesis were identified. In particular, all of the genes known to be directly involved in the repair of oxidative and alkylative damage are present in M. tuberculosis. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 74 publications
2
132
0
1
Order By: Relevance
“…Reactive oxygen and nitrogen intermediates represent more physiologically relevant DNA damaging agents (2). Nitrosative and oxidative stress conditions were modelled by exposure to acidified sodium nitrite and t -butyl hydroperoxide, respectively (Figure 1c and d), which have been shown previously to cause these types of damage (40,41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactive oxygen and nitrogen intermediates represent more physiologically relevant DNA damaging agents (2). Nitrosative and oxidative stress conditions were modelled by exposure to acidified sodium nitrite and t -butyl hydroperoxide, respectively (Figure 1c and d), which have been shown previously to cause these types of damage (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…Since persistence within the infected macrophage and reactivation of the bacillus from the dormant state are key features of infection, the maintenance of genome integrity is considered a vital aspect in the biology of M. tuberculosis (2,3). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of base excision repair (BER) pathways, dedicated to preventing such mutations, play a crucial role in restoration of genomic integrity. The genome sequences of Mycobacterium tuberculosis and Mycobacterium smegmatis have revealed that they lack the mismatch repair and the very short patch repair pathway enzymes (Cole et al, 1998;Mizrahi & Andersen, 1998). Furthermore, RecA-mediated repair also does not appear to play a significant role in mutation prevention in mycobacteria (Boshoff et al, 2003;Rand et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It not only tolerates the hostile environment within macrophages but also survives environmental stresses like exposure to UV, dehydration and low temperature during host exchanges (Manganelli et al, 2004). Although the DNA damage response mechanisms in M. tuberculosis are not well understood, it is clear that for its persistence in the host, DNA repair strategies are vital for this pathogen (Mizrahi & Andersen, 1998).…”
Section: Introductionmentioning
confidence: 99%